The Beauty Industry and Engineering Technologies - Jin Kwon, Hye; ., . (International Journal of Engineering and Technology, 2018)
This study attempted to converge beauty and engineering for the purpose of overcoming the limitations of the current emotion-centered beauty industry and creating quantitative and objective values of beauty. This study also examined engineering technologies currently in use in the cosmetics field and analyzed them in a quantitative manner. Thereby this study intends to provide basic knowledge on a new convergent study area that is broadly applicable to the beauty industry and its all related fields.Â Â